Removal of silver nanoparticles using phytoremediation method - Mad Akahir, Aida Atikah; Mat Lazim, Zainab; Salmiati, Salmiati (Universitas Nahdlatul Ulama Surabaya, 2021)
This paper presents on removal of silver nanoparticles using phytoremediation. In this study, floating macrophyte (Pistia stratiotes) was used for phytoremediation of silver nanoparticles. This study investigated the performance of Pistia stratiotes in the removal of silver nanoparticles using phytoremediation method. The silver nanoparticles were green synthesized by using Muntingia calabura sp. leaves as reducing and stabilizing agent. The silver nanoparticles were successful synthesized as a peak appeared at wavelength 450 nm by UV-Vis spectrophotometer, while Pistia stratiotes had been acclimatized in tank at laboratory. Similar size of Pistia stratiotes had been employed for investigation. Each selected Pistia stratiotes was placed in 5 L bottles water containing different concentration (0.5 ppm, 1.0 ppm, 2.0 ppm and 3.0 ppm) of silver nanoparticles. This study was evaluated using UV-Vis spectrophotometer for five days. The results showed that the highest removal was achieved 69.88% at concentration of 0.5 ppm. This percentage removal relatively decreased up to 55.61% as concentration increase at 3.0 ppm. These results prescribed that phytoremediation of silver nanoparticles by Pistia stratiotes can be considered to apply and implement in water environment for AgNPs removal.